Detection of Mycoplasma Infection of Mammalian Cells - Houhui Xia; Jamie Fitzgerald; David S. Bredt; John R. Forsayeth (BioTechniques)
Mycoplasma infection was detected in cultures of COS cells with a novel, simple assay that detects the conversion of arginine to citrulline by the enzyme, arginine deiminase, specific to all species of mycoplasma. Transfection of COS cells was inhibited in mycoplasma-infected cells, a phenomenon that was readily reversed by treatment with a mycoplasma removal agent. Cultures of cells used for transfection should be regularly monitored for evidence of mycoplasma by assay of arginine deiminase activity or by other methods.